2020
DOI: 10.1002/bbb.2135
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive calcium silicate glass synthesized from sustainable biomass wastes

Abstract: Biomass wastes of corn, sugarcane, and eggshells were used as resources to synthesize calcium silicate glass by applying the melt quench technique. The glasses were characterized by different experimental techniques to check their suitability as bioproducts. The in vitro bioactive properties of the glasses were evaluated in simulated body fluid (SBF). As confirmed by X-ray diffraction, Fourier transform infrared spectroscopy, and scanning electron microscopy, a carbonated amorphous hydroxyapatite layer was for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Shivani and Kulvir (2020) [ 25 ] produced bioactive calcium silicate glass using a melt-quenching technique. The precursors were from sugar bagasse and corn for the silica source and eggshells for the CaO source.…”
Section: Materials and Methods Of Wollastonite Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Shivani and Kulvir (2020) [ 25 ] produced bioactive calcium silicate glass using a melt-quenching technique. The precursors were from sugar bagasse and corn for the silica source and eggshells for the CaO source.…”
Section: Materials and Methods Of Wollastonite Preparationmentioning
confidence: 99%
“…The use of biomass as a renewable energy source, or for the production of biogenic materials—especially from rice husk and rice straw—has sparked a lot of interest in recent years [ 14 , 15 , 16 ]. Previous studies reported that agricultural waste is a safe substitute used as bioceramics or bioglass [ 17 , 18 , 19 ], biomaterials in bone substitution to stimulate osteoblast development [ 10 ] in medical and dental therapy [ 20 , 21 , 22 , 23 , 24 , 25 ], and anticancer drug delivery [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is not desirable to landfill eggshell waste directly due to environmental concerns. Instead, eggshell waste can be potentially reused to eliminate the environmental threat and produce a high economic value ( Xu et al, 2019 ; Mohazzab et al, 2020 ; Punj and Singh, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…These ash-derived materials are being utilized to synthesize phosphors that can be probable candidates for solid state-lighting applications. 8 The ashes of biomass waste are also being used to produce bioactive glasses, 9 glass sealants, 10 and dielectric materials. 11 Biochar prepared from biomasses can be used as an adsorbent for the treatment of wastewater containing methylene blue dye.…”
mentioning
confidence: 99%